2020
DOI: 10.2174/1566524019666191014170912
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Uterine Fibroids

Abstract: Lifestyle factors, such as alcohol intake, have placed a substantial burden on public health. Alcohol consumption is increasing globally due to several factors including easy accessibility of this addictive substance besides its legal status and social acceptability. In the US, alcohol is the third leading preventable cause of death (after tobacco, poor diet and physical inactivity) with an estimated 88,000 people dying from alcohol-related causes annually, representing 1 in 10 deaths among working adults. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Moreover, a study of 1146 premenopausal African American and Caucasian women showed that current alcohol intake in Caucasian women is associated with an increased risk of uterine fibroids compared to African Americans and nondrinkers. Although no correlation between alcohol intake and uterine fibroid risk in African Americans was found, the relationship of current and past drinking history and uterine fibroid size was generally similar among African American and White women ( 35 ).…”
Section: Environmental Exposure and Pathogenesis Of Uterine Fibroidsmentioning
confidence: 97%
See 3 more Smart Citations
“…Moreover, a study of 1146 premenopausal African American and Caucasian women showed that current alcohol intake in Caucasian women is associated with an increased risk of uterine fibroids compared to African Americans and nondrinkers. Although no correlation between alcohol intake and uterine fibroid risk in African Americans was found, the relationship of current and past drinking history and uterine fibroid size was generally similar among African American and White women ( 35 ).…”
Section: Environmental Exposure and Pathogenesis Of Uterine Fibroidsmentioning
confidence: 97%
“…Other important risk factors include obesity ( 23-25 ), vitamin D deficiency ( 26-28 ), excessive vitamin E levels ( 29 ), altered reproductive tract microbiome ( 30 ), exposure to endocrine-disrupting chemicals (eg, organophosphate esters and plasticizers) ( 31 , 32 ), and various early-life adverse environmental exposures ( 33 ). Individual and environmental risk factors associated with tobacco smoking and alcohol abuse can also contribute to the formation of uterine fibroids ( 34 , 35 ). More risk factors are associated with a higher probability of uterine fibroid formation and development ( 1 , 23 ).…”
Section: Epidemiology Risk/protective Factors Driver Mutations and Tu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the incidence of UFs has been shown to be greater in populations consuming more red meat, for example, beef [31]. The lesions have also been positively associated with the current consumption of alcohol, particularly beer [32,33], whereas a diet rich in green vegetables and citrus fruits seemed to be a protective factor [34]. Many people believe in the beneficial power of vitamins, both in isolated diseases, and for health in general.…”
Section: Diet Healthy Lifestyle and Uterine Fibroids: An Overviewmentioning
confidence: 99%